Application of Videofluoroscopy Digital Analysis in Swallowing Function Assessment for Patients with Nasopharyngeal Carcinoma after Radiotherapy - Suyue HE; Kui LI; Zulin DOU (康复学报)
Objective:To evaluate the differences of swalling function in patients with nasopharyngeal carcinoma after radiotherapy and healthy people by using digital analysis of videofluoroscopic swallowing study (VFSS).Methods:Thirteen patients with nasopharyngeal carcinoma after radiotherapy were selected as the experimental group. And ten healthy people without thistory of nasopharyngeal carcinoma radiaton and other diseases which can affect swallowing function in society were recruited as the control group. All subjects were assessed by VFSS.Results:The experimental group showed significant differences in oral transit time, soft palate elevation time, hyoid vertical displacement, as well as the opening time and range of upper esophageal sphincter (UES) compared with the control group (P<0.05).Conclusion:Using digital analysis of VFSS can quantify swallowing function, it is the golden standard test for detection of dysphagia.